Detection of Urinary Exosomal HSD11B2 mRNA Expression: A Useful Novel Tool for the Diagnostic Approach of Dysfunctional 11β-HSD2-Related Hypertension - De Santis, Domenica; Castagna, Annalisa; Danese, Elisa; Udali, Silvia; Martinelli, Nicola; Morandini, Francesca; Veneri, Mariangela; Bertolone, Lorenzo; Olivieri, Oliviero; Friso, Simonetta; Pizzolo, Francesca (Frontiers in Endocrinology, 2021)
Objective. Apparent mineralocorticoid excess (AME) is an autosomal recessive disorder caused by the 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2) enzyme deficiency, traditionally assessed by measuring either the urinary cortisol metabolites ratio (tetrahydrocortisol+allotetrahydrocortisol/tetrahydrocortisone, THF+5αTHF/THE) or the urinary cortisol/cortisone (F/E) ratio. Exosomal mRNA is an emerging diagnostic tool due to its stability in body fluids and its biological regulatory function. It is unknown whether urinary exosomal HSD11B2 mRNA is related to steroids ratio or HSD11B2 662 C>G genotype (corresponding to a 221 A>G substitution) in patients with AME and essential hypertension (EH). Aim of the study: to detect and quantify HSD11B2 mRNA from urinary exosomes in samples from family members affected by AME and EH; evaluation of the relationship between exosomal HSD11B2 mRNA, steroids ratio, 662C>G genotype and hypertension. Methods. In this observational case-control study, urinary steroids ratios and biochemical parameters were measured. Urinary exosomes were extracted from urine and exosomal HSD11B2 mRNA was quantified by Droplet Digital PCR (ddPCR). B2M (β-2 microglobulin) gene was selected as reference housekeeping gene. Results. Among family members affected by AME, exosomal urinary HSD11B2 mRNA expression was strictly related with genotypes. The two homozygous mutant probands showed the highest HSD11B2 mRNA levels (median 169 range 118-220, copies/uL) that progressively decreased in 221 AG heterozygous with hypertension (108 range 92-124 copies/uL), 221 AG heterozygous normotensives (23.35, range 8-38.7 copies/uL), wild type 221 AA subjects (5.5, range 4.5-14 copies/uL). Heterozygous hypertensive subjects had more HSD11B2 mRNA than heterozygous normotensive subjects. The F/E urinary ratio correlated with HSD11B2 mRNA copy number (p< 0.05); HSD11B2 mRNA strongly decreased while THF+5αTHF/THE increased in the two probands after therapy. In the AME family, HSD11B2 copy number correlated both with F/E and THF+5αTHF/THE ratio, whereas in EH patients a high F/E ratio reflected a reduced HSD11B2 mRNA expression. Conclusions. HSD11B2 mRNA is detectable and quantifiable in urinary exosomes; its expression varies according to the 662 C>G genotype with the highest levels in homozygous mutant subjects. The HSD11B2 mRNA overexpression in AME could be due to a compensatory mechanism of the enzyme impairment. Exosomal mRNA is a useful tool to investigate HSD11B2 dysregulation in hypertension.